PENGARUH PEMBERIAN TERAPI MUSIK KLASIK TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI DI DESA MOSSO MALUKU - Usman Barus Ohorella; Irhamdi Achmad (Jurnal Keperawatan Indonesia Timur (East Indonesian Nursing Journal), 2022)
Backgroud: Hypertension defined as an increase in abnormal blood pressure and is measured at least on three different occasions, with a result of systolic pressure> 140 mmHg and diastolic> 90 mmHg. Stroke prevalence based on Basic Health Research (2018) of 10.9% (7 % in 2013) in population over 18 years, while for hypertension in population over 18 years at 34.1% (25.8% in 2013). The increasing prevalence of the number of sufferers of hypertension is due to the lack of public knowledge about the factors that trigger the disease and the lack of efforts in preventing this disease. prevention must be tried as much as possible by controlling risk factors for hypertension. This study aims to determine the effect of classical music therapy on reducing blood pressure in hypertensive patients in Mosso Village in 20120. Method: This study uses a Quasi experimental design with a pretest posttest control with group design approach. In this design there are two groups, namely the control group and the intervention group, with the approach of using Probability sampling with a total sample of 47 people with hypertension for each group. The results indicated a significant effect of classical music therapy on reducing blood pressure (systole / distole) in hypertensive patients between the intervention group (p <0.0001) when compared to the control group (systole) (p 0.045) diastole (p 0.002). Conclusion: Classical music therapy gives effect on blood pressure, so it can be recommended as a procedural standard in reducing blood pressure in hypertensive patients.